The relations between the trade union movement and the PT governments (2003-2016) - Campos, Cauê Vieira (2019)
In this papper, we intend to address the relations developed between the Brazilian trade union movement and the Lula (2003-2010) and Dilma (2011-2016) governments of the Workers’ Party, with a primary focus on the trade union centrals, as representatives of the movement’s leadership. Starting from the idea that the rise of Lula to the presidence is a historical landmark for the country, mainly for the trade unionism - like its great representative in the decades of 1980 and 1990. We return to the economic and political measures of the government that directly influence in the market of the and trade unions, and how centrals and unions reacted to these measures. But we do not see trade union movement as merely reacting to government measures, but also part of it as a constructor, of what has become known as “concertação social.” We conclude that in this period there was a process of institutionalization and increased recognition of trade unionism as an interlocutor of the State, however to the detriment of direct action and increased separation between the leaders and workers’ bases. Resulting in the inability to resist the attacks promoted by big capital in a more difficult way after 2016. We do this, mainly through the bibliography of the area, in which there was a wide discussion on this subject, and the economic, social and unionism datas.